Determination Of Relative Error in Coal Resource Classification Based On Geostatistical Drill Hole Spacing Analysis: A Case Study of Coal Deposits at Batang Hari, Jambi - Muhammad Fadhli; Budhi Setiawan (Universitas Muslim Indonesia, 2022)
Generally, the determination of resource classification is only qualitative based on the geometric factors and geological complexity that control it. However, as the prospect area is found to have a reasonably heterogeneous sediment characteristic, a method is needed that can be used to increase the level of confidence in determining the Optimum Drill Hole Spacing. Therefore, this study uses the application of geostatistics with the global estimation variance (GEV) method based on the relative error value of each parameter, namely the thickness geometry and quality in the form of Ash and VM. This research was carried out in Jangga Aur village, Bathin XXIV District, Batang Hari Regency, Jambi Province, Working Area of PT Berkat Bara Persada Jobsite PT Inti Bara Nusalima.The Drill Hole Spacing Analysis (DHSA) results will obtain optimum spacing on resource classification based on relative error values, namely 0-10% for measured resources, 10-20% for indicated resources, and 20% for Inferred resources carried out the on-seam reference. Based on the results of the study, it was found that the seam reference used was Seam D, then the spacing distance of the drill hole on the coal seam of the research area, which had an average distance of 80 m, with geostatic analysis could be increased up to a distance of 250 m in measured resources, indicated resources of 450 m and Inferred 800 m.